Tying hands is not commitment: Can fiscal rules and institutions really enhance fiscal discipline? - Xavier Debrun (Bruegel, 2007)
This paper discusses the role of fiscal institutions, including budget rules and non-partisan agencies, in enhancing fiscal discipline. A stylized model of fiscal policy illustrates that optimal institutions lack credibility unless the costs to bypass them are sufficiently high. To the extent that the deficit bias is related to electoral uncertainty, complete budgetary transparency and strong democratic accountability suffice to establish credibility. Under incomplete budgetary transparency, accountable governments may also use institutions as a signal of competence to increase their reelection chances, which in turn erodes the penchant for excessive deficits. In light of the theory, empirical tests of the effectiveness of rules and institutions are undertaken. Looking at data for the EU-15, the estimated positive impact of numerical fiscal rules indicators on the primary balance may suffer from a simultaneity bias (because disciplined governments may be more likely to adopt strict institutions). Instrumental variable estimates fail to detect any significant effect of rules on fiscal outcomes.
Keywords: E61; E63; H62; 330; deficit bias; fiscal rules; credibility; accountability; transparency; Finanzpolitik; Haushaltsdefizit; Theorie; EU-Staaten